Miskonsepsi pada Materi Aljabar Siswa Kelas VIII SMP - Najmawati Azis; Suradi Tahmir; Ilham Minggu (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2020)
This research aimed to describe the misconception of class VIII students to solving questions in algebra material. To identify the occurrence of misconceptions in this study, using CRI (Certaninty of Respon Index) was a measure the level of confidence / certainty of respondent in answering each question (problem) given. The instrument data collection technique used was a diagnostic test with CRI criteria and interview. The research result concluded that several types of misconception indetified were (1) Student experienced concept misconception related to definition of variableand coefficient, (2) Student experienced count misconception related to the operation of like terms, (3) Student experienced sign misconception related to constant and (4) Student experienced translation misconception related to coefficient.